(untitled) (Phenomenology, Humanities and Sciences, 2023)
From an analysis and discussion of Carl R. Rogers’ considerations on the Ellen West case. The guiding question of this study is: How can the experience of loneliness, taken as a different kind of "facilitating condition," be taken as a fundamental ingredient for the constitution of a becoming oneself? In Rogers’ view, Ellen was lost in her existence because she could not hear herself in her authentically organismic expressions. She lacked a sensitive welcome and listening that could have aroused loneliness, not in its degenerate way, which is a heavy and distressing isolation of the self. However, as a unique experience of recollection to enter this authentic and organismic way of being, I propose, based on Roger’s speech, to expose other understandings of the experience of loneliness.